2013
DOI: 10.32738/jeppm.201301.0002
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insulated Panels: Past, Present, and Future

Abstract: Since the emergence of construction technology, construction of affordable and environmentally-sensible home at fast pace has brought dream home within the reach. Structural Insulated Panel (SIP) has become a topic of interest among researchers in the recent years. SIP has the advantages of minimal material wastage and labour-savingness whilst having potential to save house builders' time and money as well as retaining the controlled quality. Nonetheless, it suffers from few drawbacks which should be further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…(Reproduced from Ref. , with permission from Journal of Engineering, Project and Production Management.) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Application Of Eps In Construction Industrymentioning
confidence: 99%
“…(Reproduced from Ref. , with permission from Journal of Engineering, Project and Production Management.) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Application Of Eps In Construction Industrymentioning
confidence: 99%
“…This is a clear indication that SIPs are perceived to provide similar benefits that do pre-fabricated standard panels. Although several studies [5,7] reported that SIPs are able to reduce construction time on site, the results of the survey for builders with prior SIPs experience showed that the builders found the system more time consuming with 44% indicating that it took them longer to construct compared with 22% who indicated it was a faster system. According to the comments of the builders, lack of familiarity and understanding and too many engineering requirements and design issues are the issues which make the application of SIPs time-consuming.…”
Section: Buildermentioning
confidence: 93%
“…. Prefabricated housing has been demonstrated as a method of reducing the amount of waste material through the factory manufacturing process and reduced on-site construction waste by minimising the amount of off cut waste material, which would typically be sent to the landfill [7,15,16]. Noteworthy mentioning that the average residential construction project in New Zealand produces on average 4 tonnes of waste during the construction process, which is sent to landfills around the country [17].…”
Section: Structural Insulated Panels (Sips)mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its relatively low density with an average value of 235 kg/m 3 [2], the oil palm wood has great potential to be a good alternative to replace polymer foam core commonly used in the lightweight sandwich structures [3][4][5]. Since it is a natural material, the oil palm wood possesses a large density variation ranging from 190 kg/m 3 to 580 kg/m 3 both in the cross section and along the oil palm trunk height [6].…”
Section: Introductionmentioning
confidence: 99%